Characteristics of drowning deaths in an inner city river. (November 2020) - Stephenson, Lilli; Stockham, Peter; van den Heuvel, Corinna; Byard, Roger W.
Highlights: A study was undertaken of all drowning deaths that occurred from 1988–2017 in an urban section a river. 34 drownings (0–5 cases/yr) included 15 (44%) accidents, 11 (32%) suicides, 1 (3%) homicide and 7 (21%) undetermined. The relatively high number is related to falls while intoxicated and the availability of the river as a means of suicide. Abstract: A study was undertaken of all drowning deaths that occurred over a 30-year period from 1988 to 2017 in the urban section of the River Torrens, Adelaide, South Australia, an augmented waterway that runs through the central business district. Autopsy records from Forensic Science South Australia (FSSA) were reviewed. There were 34 drownings (0–5 cases/yr) with 28 males and 6 females (M;F = 4.6:1), with an age range for males of 18-76yrs (mean 42.0; SD 18.0) and for females of 20-84yrs (mean 69.3; SD 24.5). There were 15 (44%) accidents, 11 (32%) suicides, 1 (3%) homicide and 7 (21%) undetermined. Of the 22 cases during or after 1994 with complete toxicology reports, 10 (45%) had a blood alcohol concentration (BAC) of greater than 0.05% (g/100 mL) with an illicit substance detected in 4 (18%) cases: (MDMA (3, 4-methylenedioxymethamphetamine), methylamphetamine and THC (delta-9-tetrahydrocannabinol) acid). The presence of various therapeutic drugs was also detected in 10 cases (45%) including temazepam, fluoxetine, diazepam, olanzapine, amitriptyline, carbamazepine, codeine, citalopram and valproate. Although the numbers of cases were not high, the urban portion of the River Torrens had a much higher number of drowning events per kilometre compared to other inland waterways in South Australia such as the Murray River. This is most likely due to the vulnerability that exists for intoxicated individuals in the city from falls into the water and to the availability of the river as a means of suicide to members of the adjacent urban population.